Dong Thap university journal of science: Social sciences and Humanities issue Volume 12 - Number 3 (Dong Thap Dong Thap University, 2023)
Content: Constructing models for training, career practice for students in early training between training institutions and kindling schools, Literature review on local education for high school students,...
Keywords: Tạp chí